Transnational Death - Saramo, Samira; Koskinen-Koivisto, Eerika; Snellman, Hanna (Studia Fennica Historica, 2019)
With so much of the global population living on the move, away from their homelands, and in diasporic communities, death and mourning practices are inevitably impacted. Transnational Death brings together eleven cutting-edge articles from the emerging field of transnational death studies. By highlighting European, Asian, North American, and Middle Eastern perspectives, the collection provides timely and fresh analysis and reflection on people's changing experiences with death in the context of migration over time. First beginning with a thematic assessment of the field of transnational death studies, readers then have the opportunity to delve into case studies that examine experiences with death and mourning at a distance from the viewpoints of Family, Community, and Commemoration. The chapters highlight complicated issues confronting migrants, their families, and communities, including: negotiations of burial preferences and challenges of corpse repatriation; the financial costs of providing end-of-life care, travel at times of death, and arranging culturally appropriate funerals and religious services; as well as the emotional and sociocultural weight of mourning and commemoration from afar. Overall, Transnational Death provides new insights on identity and belonging, community reciprocity, transnational communication, and spaces of mourning and commemoration.